The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3928/15428877-20120531-03
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Complications of Hydrogel Scleral Explant Removal

Abstract: Deterioration may occur after implantation for 10 years or longer. This is due to microstructural change of the hydrogel material. The most common problems are motility disturbance and presence of a tumor-like, palpable mass under the eyelid. Removal of the implant can alleviate some ocular problems. However, RD can recur and diplopia may persist after removal of the SB. Vision usually is not affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…[9] Moreover a study by Chen et al carried out in 2012 aimed to analyze 23 patients after buckle removal and reported no visual acuity changes after buckle removal. [25] It is necessary to add that in the present study myopia was the most predisposing factor for RRD (13/15). The cause of the retinal detachment in other two patients was unknown.…”
Section: Discussionmentioning
confidence: 74%
“…[9] Moreover a study by Chen et al carried out in 2012 aimed to analyze 23 patients after buckle removal and reported no visual acuity changes after buckle removal. [25] It is necessary to add that in the present study myopia was the most predisposing factor for RRD (13/15). The cause of the retinal detachment in other two patients was unknown.…”
Section: Discussionmentioning
confidence: 74%
“… 8 In a study of 23 eyes prior to MIRAgel scleral explant removal the common reasons for removal were palpable mass under the eyelid (48%), pain and discomfort (35%), visualization of the buckle eroding through the conjunctiva (26%), diplopia (30%), complete immobility (17%), and signs of infection (17%). 9 …”
Section: Discussionmentioning
confidence: 99%
“…A wide range of RR has been reported in the literature 10,[20][21][22][23] after removal of scleral buckles, reaching as high as 34%. Reported rates of intraoperative scleral perforation reach 8% for silicone buckles and range from 0 to 18% for MIRAgel explants.…”
Section: Discussionmentioning
confidence: 99%